Three‐dimensional printing in radiation oncology: A systematic review of the literature. Issue 8 (27th May 2020) - Rooney, Michael K.; Rosenberg, David M.; Braunstein, Steve; Cunha, Adam; Damato, Antonio L.; Ehler, Eric; Pawlicki, Todd; Robar, James; Tatebe, Ken; Golden, Daniel W.
Abstract: Purpose/objectives: Three‐dimensional (3D) printing is recognized as an effective clinical and educational tool in procedurally intensive specialties. However, it has a nascent role in radiation oncology. The goal of this investigation is to clarify the extent to which 3D printing applications are currently being used in radiation oncology through a systematic review of the literature. Materials/methods: A search protocol was defined according to preferred reporting items for systematic reviews and meta‐analyses (PRISMA) guidelines. Included articles were evaluated using parameters of interest including: year and country of publication, experimental design, sample size for clinical studies, radiation oncology topic, reported outcomes, and implementation barriers or safety concerns. Results: One hundred and three publications from 2012 to 2019 met inclusion criteria. The most commonly described 3D printing applications included quality assurance phantoms (26%), brachytherapy applicators (20%), bolus (17%), preclinical animal irradiation (10%), compensators (7%), and immobilization devices (5%). Most studies were preclinical feasibility studies (63%), with few clinical investigations such as case reports or series (13%) or cohort studies (11%). The most common applications evaluated within clinical settings included brachytherapy applicators (44%) and bolus (28%). Sample sizes for clinical investigations were small (median 10, range 1–42). A minority of articles described basic or translational research (11%) and workflow or cost evaluation studies (3%). The number of articles increased over time ( P  < 0.0001). While outcomes were heterogeneous, most studies reported successful implementation of accurate and cost‐effective 3D printing methods. Conclusions: Three‐dimensional printing is rapidly growing in radiation oncology and has been implemented effectively in a diverse array of applications. Although the number of 3D printing publications has steadily risen, the majority of current reports are preclinical in nature and the few clinical studies that do exist report on small sample sizes. Further dissemination of ongoing investigations describing the clinical application of developed 3D printing technologies in larger cohorts is warranted.